Health Attitudes in Youth: a Cross-cultural Analysis of Associative Responses - Kostruba, Nataliia S. (My University, 2025)
The purpose of this article is to make an empirical analysis of associative reactions of young people from Ukraine and Congo to the concept of «health». Methods of the research. We used Linguistic Inquiry and Word Count (LIWC) software to empirically study the resulting associative responses. The survey resulted in 73 different associations, which were further analyzed by categories: emotions, cognitive processes, perception, relativity, etc. The results of the research. According to the results of comparing associative reactions to “health” in students from Ukraine and Congo according to the criterion of emotions, we found that the indicators of emotional attitude to health are much higher among students from Congo (32.43) than among students from Ukraine (4.62); in the social context it is shown that the indicators of the social aspect of health are 1.54 among Ukrainian students and zero for Congolese; in the cognition context, the indicators demonstrate a greater tendency to cognitively assess one’s own health in Congolese students (18.92) than in Ukrainian students (1.5); in the context of perception, Congolese youth demonstrate higher indicators 2.70 than Ukrainian students 1.54; in the context of biological accents, it was found that Congolese students more often turn to this topic when reviewing the concept of “health” (16.22) than Ukrainian students (1.54); in the context of motivation or need, such indicators were recorded only among Ukrainian students in terms of motivation in relation to health (1.54). Conclusions. Empirical analysis of associations for “health” in groups of young people from Ukraine and Congo was conducted using LIWC-2015 and it demonstrated a number of differences. Ukrainian students are more likely to use less emotional associations that are more related to relativity and solving health problems, namely “Hospital”, “medicine”, “harmony”, etc. Students from Congo are more likely to use associations with a more emotional response, mainly negative, as well as reactions related to health problems and their evaluation. Young people from Congo often use associations such as “illness”, “evil”, “fear”, “good”, etc.
Keywords: health; associative experiment; youth; health literacy; LIWC- 2015; 159.95: 613.8